Adherence to public institutions that foster cooperation - Arunas L. Radzvilavicius (Nature Portfolio, 2021)
Here, the authors examine how altruism can emerge as people come to trust a public institution of moral assessment, which broadcasts whether individuals have good or bad reputations for reciprocity.